Youth Perceptions of Law Enforcement and Worry About Crime from 1976 to 2016 - Fine, Adam D. (Criminal justice and behavior, 2020)
Recent unjust interactions between law enforcement and youth of color may have provoked a “crisis” in American law enforcement. Utilizing Monitoring the Future’s data on distinct, cross-sectional cohorts of 12th graders from each year spanning 1976-2016, we examined whether youth perceptions of law enforcement have changed. We also traced youth worry about crime considering declining perceptions of law enforcement may correspond with increasing worry about crime. Across decades, White youth consistently perceived law enforcement the most positively and worried least about crime, followed by Hispanic/Latinx then Black/African American youth. During the 1990s, among all youth, perceptions of law enforcement declined while worry about crime increased. However, recently, such trends were limited to White youth; among youth of color, perceptions of law enforcement declined while worry about crime remained largely stable. Problematically, youth perceptions of law enforcement recently reached a decades-long low and racial/ethnic gaps in perceptions appear to be growing.